Accessing Justice: The Role of Law School Legal Clinics in Conflict-affected Societies. (July 2014) - Grimes, Richard
This article looks at access to justice in the context of histories, past or present, of armed conflict and civil strife. It takes, as its starting point, the importance of the rule of law as one of the means, if not the only (or even most suitable), of rendering accountable those who violate rights and prevent the uptake of entitlements. Given the relative lack of infrastructure in many jurisdictions, it is often problematic for indigent people to secure legal help. To address such unmet needs, non-governmental organizations (NGOs) and legal educators (and in some instances government departments) are coming together to establish legal clinics through which clients and communities can be assisted. Where these clinics are based in or are otherwise being supported by law schools, students under professional supervision, not only help the poor and the needy but also develop their own knowledge, skills and values by applying principle to practice. The article draws on the author's direct experience in countries emerging from conflict and asks, to what extent can legal clinics provide an appropriate, relevant and sustainable service that meets the needs of all stakeholders? Also, it seeks to address whether there are lessons to be learnt from observed developments and if there is a 'clinical' model that can be adapted and implemented in jurisdictions where access to justice is a major challenge.